Exceptions to the rule not to allocate public revenue - عبدالقادر بان صلاح; نعمة رغد عبدالله (Journal of Legal Sciences, 2021)
The general budget is the state’s annual financial program that manages public facilities and services in it، which contains public earning and expenses. The general budget is subject to several principles. The most important of these principles is the principle of generality، watch includes the proper management of the financial program through two basic principles the principle of allocating public expenditures and the principle of not allocating revenues.